O Pêndulo das Marés. Variações abióticas e a ictiofauna: influência de fatores ambientais na assembleia de peixes de um ecossistema marinho raso no Sul do Brasil - Costa, Rafael Maribelto da (Universidade Federal de São Carlos, 2024)
The present study investigated how environmental variations modulate the composition and functional diversity of the ichthyofauna in a shallow coastal ecosystem within the influence area of the Port of Imbituba, adjacent to the Southern Right Whale Environmental Protection Area (APABF) in southern Brazil. Based on a nearly decade-long time series (2015–2024), abiotic variables such as sea surface temperature, salinity, turbidity, and dissolved oxygen were analyzed through the lens of community assembly theory. The results showed that seasonality and interannual oscillations play central roles in structuring fish communities, with temperature and salinity acting as the main environmental filters. Turbidity, in turn, directly influenced the base of the food chain and favored generalist species. Functional diversity metrics, such as functional dispersion (FDis) and functional richness, highlighted the importance of functional diversity for community resilience in the face of environmental changes. Among the 81 recorded species, Stellifer rastrifer, Paralonchurus brasiliensis, and Isopisthus parvipinnis emerged as core species, playing critical roles in trophic networks due to their abundance and frequency of occurrence. Conversely, occasional species such as Gymnura micrura and Hypanus guttatus acted as biodiversity reservoirs under disturbance scenarios. Anthropogenic impacts, including increased turbidity caused by port sedimentation and maritime traffic, combined with climatic extremes such as marine heatwaves, posed direct threats to sensitive trophic guilds, particularly herbivores and planktivores, compromising the functional stability of the ichthyofauna. This study provides critical insights for management and conservation strategies, highlighting the need to integrate functional diversity into adaptive approaches to address increasing anthropogenic and climatic pressures. The findings reinforce the role of functional conservation in mitigating impacts and ensuring the sustainability of protected coastal marine ecosystems, such as the APABF.
The Tidal Pendulum. Abiotic variations and ichthyofauna: influence of environmental factors on the fish assemblage of a shallow marine ecosystem in Southern Brazil
Keywords: Diversidade taxonômica; Diversidade funcional; Montagem de comunidades; Variação ambiental; Resiliência ecológica; Conservação marinha; Taxonomic diversity; Functional Diversity; Community assembly; Environmental variation; Ecological resilience; Marine conservation; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA::OCEANOGRAFIA BIOLOGICA